(3GdSdhc GdJfXjej aj efXeGJ GdCYeGd (B/s - (3LhGO, Thbj fGLjs ((3YeGf(B: s (3OGQ GdMGeO ddfTQ hGdJhRjY(B, s, 2010)
(3GdSdhc GdJfXjej h GdSdhc GdGfSGfj, GdOGaYjI h GdJQZjH ddYed , GdJYde h GdJKbja, CfTWI CNQi PGJ GfYcGSGJ SdhcjI dOi GdGaQGO, GdJYGed eY GdGNQjf, GdKbGaI, GdJMhd eONd JZjjQ GdaQO h JWhQg, ehVhYGJ Yf WHjYI GdHTQjIs
Keywords: (3EOGQI GdCYeGds; (3GdSdhc GdEOGQjs; (3JfXje hEOGQIs